Aplikasi Web Pelayanan Kesehatan Masyarakat Di Kelurahan Singonegaran Dengan Metode Rapid Aplication Development - Djuniharto Djuniharto; Jihan Yulia Dewi (Jurnal Informatika dan Komputer, 2022)
Health services to the community are the duties of the Public Health Center (Puskesmas) formed by the government. However, it cannot reach the entire community. Posyandu to be formed to carry out community self-help activities in the health sector carried out in the Kelurahan. Singonegaran Village is one that has a posyandu to serve public health in its environment. In serving the health of the community, it is necessary to process data. Data processing is carried out by cadres and health workers. Data processing carried out by cadres at Posyandu Kelurahan Singnegaran still uses book recording methods. This resulted in several problems such as the process of inputting, processing and retrieving old data. Therefore we need a system or application that can overcome these problems. Then a web-based health service application was made in Singnegara Village. The development of public health service applications in Singonegaran Village uses the Rapid Application Development (RAD) development method with the blackbox testing method. From the results of the application development it was declared successful in testing.